Development of High-Performance Memory Chip Industry - Liu Meng (中国工程科学)
High-performance storage chips are the core driving force underlying the robust expansion of global artificial intelligence. They are crucial for promoting the information technology industry, improving the performance of electronic devices, driving the evolution of servers and data centers, and fostering nascent technologies such as artificial intelligence, machine learning, the Internet of Things, virtual reality, and augmented reality. This study explores the essence of high-performance storage chips and sorts out their development requirements and international development trend. Moreover, it summarizes the development status of high-performance storage chips in China, delves into the problems and challenges encountered, and pinpoints the transformative opportunities. Furthermore, it proposes the following policy suggestions: (1) implementing a stratified approach to solidify the foundation while revolutionizing strategies to strive for breakthroughs; (2) stressing on both traditional and novel technologies and pursuing parallel development along multiple pathways; and (3) accelerating the establishment of a novel technological framework to progressively break the market monopoly.